Connecting Main-Group Metals (Al, Ga, In) and Tungsten(0) Carbonyls via the N2S2 Metallo-Ligand Strategy - Xuemei Yang; Allen Lunsford; Marcetta Y. Darensbourg (Inorganics, 2019)
Tetradentate N2S2 ligands (such as bismercaptoethanediazacycloheptane in this study) have seen extensive use in combination with transition metals. Well-oriented N2S2 binding sites are ideal for d8 transition metals with square planar preferences, especially NiII, but also as a square pyramidal base for those metals with pentacoordinate preferences, such as [V≡O]2+, [Fe(NO)]2+, and [Co(NO)]2+. Further reactivity at the thiolate sulfurs generates diverse bi, tri, and tetra/heterometallic compounds. Few N2S2 ligands have been explored to investigate the possibility of binding to main group metals, especially group III (MIII) metals, and their utility as synthons for main group/transition metal bimetallic complexes. To open up this area of chemistry, we synthesized three new five-coordinate main group XMN2S2 complexes with methyl as the fifth binding ligand for M = Al, and chloride for M = Ga and In. The seven-membered diazacycle, dach, was engaged as a rigid stabilized connector between the terminal thiolate sulfurs. The pentacoordinate XMN2S2 complexes were characterized by 1H-NMR, 13C-NMR, +ESI-Mass spectra, and X-ray diffraction. Their stabilities and reactivities were probed by adding NiII sources and W(CO)5(THF). The former replaces the main group metals in all cases in the N2S2 coordination environment, demonstrating the weak coordinate bonds of MIII−N/S. The reaction of XMN2S2 (XM = ClGaIII or ClInIII) with the labile ligand W(0) complex W(CO)5(THF) resulted in Ga/In−W bimetallic complexes with a thiolate S-bridge. The synthesis of XMN2S2 complexes provide examples of MIII−S coordination, especially Al−S, which is relatively rare. The bimetallic Ga/In−S−W complex formation indicates that the nucleophilic ability of sulfur is retained in MIII−S−R, resulting in the ability of main group MIII−N2S2 complexes to serve as metalloligands.